Ancient Town-Planning - Haverfield, F. (Francis), 1860-1919 (Salt Lake City, UT : Project Gutenberg, 2004)
"Ancient Town-Planning" by F. Haverfield is a scholarly work published in the early 20th century. The book expands on a lecture presented in 1910, examining the principles and practices behind town-planning in ancient societies, particularly focusing on Greek and Roman urban design. Haverfield discusses how ancient town-planning reflects not only architectural creativity but also the social and political contexts in which these towns were developed, highlighting the evolution of concepts and methodologies through various eras. The opening of the text gives readers insight into the author's perspective as he sets the stage for an exploration of historical town-planning methods. Haverfield positions town-planning as an artform that emerged from a need for organized urban living, emphasizing its contrast with traditional political concerns. He notes that as civilizations progressed, the planning of towns became crucial for addressing the health and comfort of inhabitants. Through an analysis of historical sources and archaeological evidence, the author outlines the early practices of urban planning, mentioning notable cities and their layouts, and foreshadows a detailed discussion of how these structures facilitated not just practicality but also aesthetic and social coherence in ancient life. (This is an automatically generated summary.)
Release date is 2004-11-28
Produced by Ted Garvin and the PG Online Distributed Proofreading Team
Keywords: City planning; Cities and towns, Ancient